CAR T Cell Therapy’s Potential for Pediatric Brain Tumors - Pauline Thomas (MDPI AG, 2021)
Malignant central nervous system tumors are the leading cause of cancer death in children. Progress in high-throughput molecular techniques has increased the molecular understanding of these tumors, but the outcomes are still poor. Even when efficacious, surgery, radiation, and chemotherapy cause neurologic and neurocognitive morbidity. Adoptive cell therapy with autologous CD19 chimeric antigen receptor T cells (CAR T) has demonstrated remarkable remission rates in patients with relapsed refractory B cell malignancies. Unfortunately, tumor heterogeneity, the identification of appropriate target antigens, and location in a growing brain behind the blood–brain barrier within a specific suppressive immune microenvironment restrict the efficacy of this strategy in pediatric neuro-oncology. In addition, the vulnerability of the brain to unrepairable tissue damage raises important safety concerns. Recent preclinical findings, however, have provided a strong rationale for clinical trials of this approach in patients. Here, we examine the most important challenges associated with the development of CAR T cell immunotherapy and further present the latest preclinical strategies intending to optimize genetically engineered T cells’ efficiency and safety in the field of pediatric neuro-oncology.